Perkembangan Bahasa Anak dan Implikasinya dalam Pembelajaran - M. Syahran Jailani (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2018)
This article aims to discuss the importance of language, where language is the ability to communicate with others. Language is an essential factor that distinguishes humans from animals. Language is closely related to individual thinking development. The development of individual thinking appears in the development of language, namely the ability to form understanding, compile opinions and draw conclusions. Whereas, development is a process that must be experienced by each individual, this development is qualitative and related to maturity and systematic. Language development in children is very important because through language, children can express thoughts, so that others understand it and create a social relationship. So, it is not surprising that language is considered as an indicator of a child's success